IMPLEMENTATION OF HYPNOBIRTHING METHOD TO PREVENT PARTUS PREMATURUS IMMINENS IN FACTORY WORKER MOTHERS - Rachmad Saleh, Sri Andarini, Tita Hariyanti, I Wayan Arsana Wiyasa (South Eastern European Journal of Public Health, 2024)
Partus prematurus imminens (PPI) is a high risk for pregnant women working in factories, with stress and physical workload as the main factors. This study aims to evaluate the effectiveness of hypnobirthing method in reducing the risk of PPI in factory working mothers. Using a descriptive design and quasi-experiment, the subjects consisted of pregnant women working in factories in Sidoarjo. Hypnobirthing intervention was given to the experimental group, while the control group only received standard care. The results showed that hypnobirthing decreased stress levels, and significantly reduced cervical contractions and opening. These findings indicate that hypnobirthing has the potential to be an effective non-pharmacological prevention method for IOP, with a positive impact on maternal mental and physical health. The implication of this study is the need for integration of hypnobirthing in maternal health services, especially for mothers who work in sectors with high physical load.